2019
DOI: 10.3389/fpls.2019.01161
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Rice Diversity in the Guianas

Abstract: Traditional crop varieties are an important source of genetic diversity for crop adaptation and modern breeding. Landraces of Asian (Oryza sativa) and African (Oryza glaberrima) rice have been well studied on the continents where they were domesticated. However, their history of cultivation in northern South America is poorly understood. Here, we reveal the rice diversity that is maintained by Maroons, descendants of enslaved Africans who fled to the interior forests of the Guianas ca. 300 years ago. We interv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones. While we do not compare these alternative probes, the results from our study, Larridon et al (2020) and Murphy et al (2020) suggest that an appropriately designed universal probe set can capture adequate phylogenomic information to resolve relationships at the species-level and even at the population-level (Van Andel et al, 2019). Liu et al (2019) showed experimentally that when probes are <30% divergent from regions targeted, enrichment worked adequately (see Figure 6 and Supplementary Figure S6 in Liu et al, 2019).…”
Section: Efficacy Of Universal Probesmentioning
confidence: 78%
See 1 more Smart Citation
“…Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones. While we do not compare these alternative probes, the results from our study, Larridon et al (2020) and Murphy et al (2020) suggest that an appropriately designed universal probe set can capture adequate phylogenomic information to resolve relationships at the species-level and even at the population-level (Van Andel et al, 2019). Liu et al (2019) showed experimentally that when probes are <30% divergent from regions targeted, enrichment worked adequately (see Figure 6 and Supplementary Figure S6 in Liu et al, 2019).…”
Section: Efficacy Of Universal Probesmentioning
confidence: 78%
“…To overcome this design and optimization hurdle, the Angiosperms-353 probe set was developed from available transcriptome and genome data (One Thousand Plant Transcriptomes Initiative, 2019)including twelve Apiales representatives, three of them (Hedera, Hydrocotyle, and Polyscias) in Araliaceae -with universal probes that capture 353 nuclear single-copy loci shared across all angiosperms (Johnson et al, 2018). By using the Angiosperms-353 sequence capture probes, our study is among the first to test the efficacy of this probe set to resolve species-level relationships from either historical herbarium specimens (Brewer et al, 2019;Larridon et al, 2020;Murphy et al, 2020) or fresh tissue (Van Andel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Angiosperms353 markers seem to resolve the phylogenies of rapidly radiating groups well (Larridon et al, 2020;Shee et al, 2020) and show potential for resolving from deep (Johnson et al, 2019) to shallow phylogenetic scales, even resolving within-species relationships (Van Andel et al, 2019;Murphy et al, 2020), but their utility has not yet been fully evaluated. To date, only one study has compared the benefits of Angiosperms353 with those of a custom probe set (Larridon et al, 2020).…”
mentioning
confidence: 99%
“…Johnson et al (2019) showed an average recovery of ~283 loci per species for the Angiosperms353 probe set, and at least 100 loci for over 600 angiosperm species, but this can be increased further using the pipeline recently described by McLay et al (2021). It has been successfully implemented with low-quality material such as herbarium specimens (Brewer et al, 2019;Shee et al, 2020) and performed well for resolving shallow-level relationships (e.g., radiations [Larridon et al, 2020;Shee et al, 2020] and even at the intraspecific level [Van Andel et al, 2020;Beck et al, 2021;Slimp et al, 2021]). A few studies have compared the performance of Angiosperms353 with other taxon-specific probe sets (e.g., in Cyperus L. [Larridon et al, 2020], in the subtribe Malinae of the Rosaceae [Ufimov et al, 2021], and in the Ochnaceae [Shah et al, 2021]), but only Larridon et al (2020) directly tested the mergeability of different data sets.…”
mentioning
confidence: 99%